Коммунальные ФПГ. Новая эффективность - Лобанов, П.В. (Інститут економіко-правових досліджень НАН України, 2008)
Рассмотрены вопросы существующего кризисного состояния городского ЖКХ, проведен анализ предпринимаемых мер по его реформированию. Предложено использовать организационные структуры коммунальных ФПГ как способ повышения эффективности городского ЖКХ. Розглянуто питання існуючого кризового стану міського ЖКГ, проведено аналіз впроваджуваних заходів щодо його реформування. Запропоновано використання організаційних структур комунальних ФПГ як спосіб підвищення ефективності міського ЖКГ. The issues of crisis situation in housing and communal services are examined; analysis of measures taken to reform them is conducted. Use of organizational structures of communal financial and industrial groups (FIG) as the method for increasing city’s housing and communal services is suggested.